Usaha Pembesaran Ikan Lele Sangkuriang (Clarias gariepinus) Dengan Pakan Alternatif Limbah Pemotongan Ayam Di Kecamatan Bonang Kabupaten Demak: Analysis of Sangkuriang Catfish (Clarias gariepinus) Fishing Enterprise With Alternative Feeding of Chicken Slaughtering Waste In Bonang District Demak Regency - Wahyuningsih, Sri (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2026)
The problem with catfish farmers is that the price of manufactured feed continues to increase, to overcome the problem of alternative feeding of chicken slaughtering waste is a solution. This study aims to analyze feed, costs, revenue, income, and feasibility of raising Sangkuriang catfish with alternative feed from chicken slaughtering waste in Bonang District, Demak Regency. The basic method used in this study is descriptive analysis, a method that allows for quick identification of input data for analysis in order to analyze business conditions over a period of three months. Respondents were selected using purposive sampling. The results showed the lowest feed price of chicken slaughtering waste was Rp1,000/Kg with no price increase. The total cost of the combination group was Rp211,305,176, the chicken slaughtering waste group was Rp95,958,288, and the pellet group was Rp128,813,588. Receipts in the combination feed group amounted to Rp322,749,478, the chicken slaughtering waste group Rp252,392,315, and the pellet group Rp158,400,000. Combination feed income amounted to Rp116,923,866, chicken slaughtering waste group Rp170,342,453, and pellet group Rp44,778,744. The results of the R/C value of the combination feed group 1.53, the chicken slaughtering waste group 2.63, and the pellet group 1.23, based on these results it is concluded that the sangkuriang catfish enlargement business is declared feasible.